Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1968
DOI: 10.1136/bjo.52.4.322
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary adenoma. Preoperative symptomatology in a series of 260 patients.

Abstract: STUDY of the syndromes associated with pituitary adenoma began with the description of acromegaly by Marie (1886), and many reports of the symptomatology of the tumour have since appeared (Cushing, 1912;Cairns, 1935;Henderson, 1939;Jefferson, 1940;Bakay, 1950;Younghusband, Horrax, Hurxthal, Hare, and Poppen, 1952;Nurnberger and Korey, 1953; Mogensen, 1957;Ray and Patterson, 1962;Poppen, 1963). Recently a series of 260 patients with pituitary adenoma selected for combined surgery and radiotherapy because of fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
2
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 15 publications
(9 reference statements)
1
24
2
1
Order By: Relevance
“…5,6,11,12 Elkington described the preoperative symptomatology of patients with pituitary adenoma, and was the first to attribute the symptom to his patients' inability to correctly register an image in each eye. 13 In his series, 170 of 260 patients had bitemporal visual field loss and 84 of those (49%) complained of diplopia without having ocular palsy. 13 Hemifield slide is also possible with other heteronymous hemianopias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,11,12 Elkington described the preoperative symptomatology of patients with pituitary adenoma, and was the first to attribute the symptom to his patients' inability to correctly register an image in each eye. 13 In his series, 170 of 260 patients had bitemporal visual field loss and 84 of those (49%) complained of diplopia without having ocular palsy. 13 Hemifield slide is also possible with other heteronymous hemianopias.…”
Section: Discussionmentioning
confidence: 99%
“…13 In his series, 170 of 260 patients had bitemporal visual field loss and 84 of those (49%) complained of diplopia without having ocular palsy. 13 Hemifield slide is also possible with other heteronymous hemianopias. Borchert et al reported two patients in whom hemifield slide was attributed to heteronymous altitudinal visual field defects (those respecting the horizontal midline) from bilateral ischaemic optic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Visual field defects are thought to be due to the direct compression or the effect on the blood supply of the optic chiasm. These visual field defects can be detected by manual perimetry, 1 and by automated static perimetry.…”
mentioning
confidence: 99%
“…As well as visual dysfunction, complications include the effects of hormone hypersecretion, hypopituitarism, headaches, and epilepsy. 2 The diagnosis of this type of lesion at an early stage is therefore of importance to the prognosis of the patient, particularly as early intervention is of known benefit. [3][4][5][6] The management of patients with pituitary tumours includes surgical and medical treatments, and both have been shown to be beneficial to patients with pituitary tumour in terms of preservation of vision and amelioration of visual dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…7 The typical field defects of bitemporal hemianopias and quadrantanopias are known to be associated with pituitary tumour, although other types of field defect have been described. [8][9][10][11][12][13] Elkington 2 reported visual field defects in 92.6% of his series, with the majority (70.7%) being varieties of bilateral temporal loss. Rowe and colleagues 14 reported visual field defects in 56% of their cases, with bilateral field loss being most frequent but a mix of temporal and nasal loss.…”
Section: Introductionmentioning
confidence: 99%